Thinned Planar Array Design Using Boolean PSO With Velocity Mutation - Deligkaris, Kosmas V.; Zaharis, Zaharias D.; Kampitaki, Dimitra G.; Goudos, Sotirios K.; Rekanos, Ioannis T.; Spasos, Michalis N. (IEEE transactions on magnetics, 2009)
The design of thinned planar microstrip arrays under specific constraints concerning the impedance-matching condition of the array elements and the radiation pattern is presented. The radiation characteristics of the structure are extracted by applying the method-of-moments. The array design is based on a novel optimization method, which is a modified version of the boolean particle swarm optimization that employs velocity mutation (BPSO-vm). Apart from the optimization of the array geometry, the proposed method is applicable to other discrete-variable optimization problems. Moreover, the planar array design is coped with by means of other techniques, namely, a binary coded Genetic Algorithm, the binary Particle Swarm Optimization, and the Boolean PSO. The comparison of the above methods and the BPSO-vm shows the efficiency of the proposed technique.